2015
DOI: 10.11648/j.ijmsa.20150405.17
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Silver Nanoparticles: Synthesis Methods, Properties and Applications

Abstract: In recent years, nanoparticles of noble metals such as gold, silver and palladium have drawn immense attention due to the wide range of new applications in various fields of industry. Particularly, silver nanoparticles have significant interest in medical applications such as very effective antibacterial agents without the toxic effects, and industry application such as inkjet inks containing well uniform dispersions of nano-sized silver particles that are useful for producing electronic circuits. It is import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
144
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(148 citation statements)
references
References 52 publications
0
144
0
4
Order By: Relevance
“…Silver nanoparticles (AgNPs) are among the most popular NPs known for their strong antimicrobial and disinfectant properties [6,7]. The antibacterial activity of AgNPs has led to their extensive use in various household products such as self-sanitizing toothbrushes and bacteria -resistant stuffed toys.…”
Section: The In Vitro Effect Of Polyvinylpyrrolidone and Citrate Coatmentioning
confidence: 99%
“…Silver nanoparticles (AgNPs) are among the most popular NPs known for their strong antimicrobial and disinfectant properties [6,7]. The antibacterial activity of AgNPs has led to their extensive use in various household products such as self-sanitizing toothbrushes and bacteria -resistant stuffed toys.…”
Section: The In Vitro Effect Of Polyvinylpyrrolidone and Citrate Coatmentioning
confidence: 99%
“…[16][17][18] The physical method has several drawbacks, for example, it usually requires high energy consumption and high cost due to the use of some modern equipment. 19 In the other hand, the chemical method requires inorganic chemical which harmful to the environment. 20 In our study, we developed the simple green chemistry method to synthesize Ag-np.…”
Section: Introductionmentioning
confidence: 99%
“…The most new promising nanomaterials with antibacterial properties are the metallic nanoparticles such as silver nanoparticles [6]. Silver nanoparticles are from a long time known for many researchers, and in this direction were published excellent reviews in the last two years [7][8][9][10][11][12][13][14][15]. Few reviews were reported on biogenic AgCl nanoparticles [16].…”
Section: Introductionmentioning
confidence: 99%